Selling the pampas. The imaginary of modernization and propagandistic photography in the National Territory of La Pampa (Quinto Sol, 2011)
By the late 19th century the discourse of modernity was used by business sectors in the National Territory of La Pampa, for attracting investments and labor force oriented to their colonization and production initiatives. Photography played a core role in legitimating modernization project, by providing an arsenal of images that documented the economic developments and the general progress of the Territory, but also by contributing to resignify a space associated to “desert” and barbarism.Through the analysis of two photograph albums produced in La Pampa in the early 20th century, this article deals with the way that photography was used for propagandistic purposes appealing to social imaginaries related to progress and modernization. However, each album was produced in a different social context, in which not only economic and social conditions varied, as the way modernization project was perceived by society did.
Keywords: modernization; photography; social imaginaries; space resignification; legitimation